2015
DOI: 10.1371/journal.pone.0129425
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Tat Protein Induces Production of Proinflammatory Cytokines by Human Dendritic Cells and Monocytes/Macrophages through Engagement of TLR4-MD2-CD14 Complex and Activation of NF-κB Pathway

Abstract: We recently reported that the human immunodeficiency virus type-1 (HIV-1) Tat protein induced the expression of programmed death ligand-1 (PD-L1) on dendritic cells (DCs) through a TLR4 pathway. However, the underlying mechanisms by which HIV-1 Tat protein induces the abnormal hyper-activation of the immune system seen in HIV-1 infected patients remain to be fully elucidated. In the present study, we report that HIV-1 Tat protein induced the production of significant amounts of the pro-inflammatory IL-6 and IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 108 publications
2
43
0
Order By: Relevance
“…4B). The latter result is in agreement with our previous data showing that the Tat 1-45 mutant was also able to stimulate the TLR4 pathway (21,22). The degradation of MAL/ TIRAP following Tat stimulation seems to be related to its proteasomal degradation.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…4B). The latter result is in agreement with our previous data showing that the Tat 1-45 mutant was also able to stimulate the TLR4 pathway (21,22). The degradation of MAL/ TIRAP following Tat stimulation seems to be related to its proteasomal degradation.…”
Section: Resultssupporting
confidence: 93%
“…In previous work, we showed that Tat activates NF-B in a TLR4-dependent manner (22). Downstream of TLR4 activation, MyD88 and MAL/TIRAP work together to mediate the early activation of NF-B, while the TRIF pathway is involved in the late phase of NF-B activation.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations